Hermite–Hadamard inequalities for generalized σ−conformable integrals generated by co-ordinated functions - Çi̇ri̇ş, Sümeyye Ermeydan; Yildirim, Hüseyin (Chaos, solitons and fractals, 2024)
In this paper, we define generalized σ− conformable fractional integrals on co-ordinated functions and generalized σ−conformable fractional integrals for the functions of two variables. Furthermore, we obtain a new Hermite–Hadamard inequality by using the generalized Riemann–Liouville integrals by means of the generalized σ− conformable integral definition. Moreover, we demonstrate some consequences by utilizing Hermite–Hadamard inequality and by utilizing definitions which we define in the study. Additionally, we state and prove some inequalities.